2019
DOI: 10.1177/1045389x19828828
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-mechanical characterization of magnetorheological elastomers

Abstract: This work analyses the properties and the magneto-mechanical characteristics of magnetorheological elastomers, a class of smart materials not yet broadly investigated. First, set of several samples of this material was manufactured, each one characterized by a different percentage of ferromagnetic material inside the viscoelastic matrix. The specimens were manufactured in order to create isotropic and anisotropic configurations, respectively, with randomly dispersed ferromagnetic particles or with an aligned d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
0
14
1
Order By: Relevance
“…It has been reported that anisotropic MREs with greater iron particle volume fraction yield properties comparable to those of the isotropic MRE with the same particle volume fraction (Schubert and Harrison, 2015). Reported studies have also suggested that relatively small increase in the relative MR effect of the anisotropic MRE compared with those of the isotropic MRE, especially for relatively higher particle volume fractions of about 30% (Bellelli and Spaggiari, 2019; Lee et al, 2018). On the other hand, MREs containing <30% volume particle fraction may be damaged under the stress of the absorber mass or weight of structure that MRE is going to support (Lerner and Cunefare, 2007).…”
Section: Bi-directional Mre Isolator Designmentioning
confidence: 99%
“…It has been reported that anisotropic MREs with greater iron particle volume fraction yield properties comparable to those of the isotropic MRE with the same particle volume fraction (Schubert and Harrison, 2015). Reported studies have also suggested that relatively small increase in the relative MR effect of the anisotropic MRE compared with those of the isotropic MRE, especially for relatively higher particle volume fractions of about 30% (Bellelli and Spaggiari, 2019; Lee et al, 2018). On the other hand, MREs containing <30% volume particle fraction may be damaged under the stress of the absorber mass or weight of structure that MRE is going to support (Lerner and Cunefare, 2007).…”
Section: Bi-directional Mre Isolator Designmentioning
confidence: 99%
“…MREs overcome the problems that accompany the applications of magnetorheological (MR) fluids, such as sedimentation of particles, sealing issues, and environmental contamination. The magnetic properties of MREs originate from microstructural interactions under a magnetic field and depend on different parameters such as volume fraction and spatial distribution of embedded ferromagnetic particles [1][2][3]. When exposed to an external magnetic field, MRE changes its dynamic properties, including both stiffness and damping, rapidly and reversibly, thus, making it an ideal candidate for the development of the next generation of adaptive devices with controllable operating frequency and damping [4].…”
Section: Introductionmentioning
confidence: 99%
“…Only few works tackles the fatigue properties (Calabrò, 2011; Zhou, 2016; Zhou et al, 2017) mostly in biaxial condition while it is difficult to find information on the ultimate shear strength of MRE. This paper therefore investigates a MRE made from a silicone-elastomeric matrix, a combination already studied in literature, (Bellelli and Spaggiari, 2019; Choi et al, 2018), by considering several weight fractions, the applied magnetic field and the isotropicity of the material, by testing it dynamically at several shear rates and also up to failure, in order to estimate the effect of the variables on the material performance. A straightforward magneto-mechanical phenomenological model is proposed to estimate the behavior of the material in different conditions in terms of stiffness, ultimate shear stress and specific dissipated energy.…”
Section: Introductionmentioning
confidence: 99%